2016
DOI: 10.15694/mep.2016.000115
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Simulation in Teaching Clinical Breast Examination

Abstract: Problem: Clinical Breast Examination (CBE) is traditionally taught to third year medical students using a lecture and a table-top breast model. The opportunity to clinically practice CBE depends on patient availability and willingness to be examined by students, especially in culturally sensitive environments. Intervention:We employed hybrid simulation of the breast and aimed to investigate its effectiveness as an educational tool for teaching CBE to medical students. The hybrid simulation model consists of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Currently, there is no evidence in the literature on the effectiveness of hybrid simulation in teaching CBE to residents, nor studies that focus on assessing the educational experience of residents while performing CBE. A similar study [8] was conducted by the principle investigator which found that hybrid simulation improved lesion identification (p<0.001) and relieved the fear of missing a lesion on CBE (p=0.043) and increased satisfaction with the teaching method among medical students (p=0.002) [8]. This study is the first of its kind to use modern techniques to elevate the proficiency of residents' CBE skills and make the teaching of CBE to residents, and potentially the detection of breast cancer lesions, more rounded and even more effective.…”
Section: Significancementioning
confidence: 74%
See 2 more Smart Citations
“…Currently, there is no evidence in the literature on the effectiveness of hybrid simulation in teaching CBE to residents, nor studies that focus on assessing the educational experience of residents while performing CBE. A similar study [8] was conducted by the principle investigator which found that hybrid simulation improved lesion identification (p<0.001) and relieved the fear of missing a lesion on CBE (p=0.043) and increased satisfaction with the teaching method among medical students (p=0.002) [8]. This study is the first of its kind to use modern techniques to elevate the proficiency of residents' CBE skills and make the teaching of CBE to residents, and potentially the detection of breast cancer lesions, more rounded and even more effective.…”
Section: Significancementioning
confidence: 74%
“…We employed hybrid simulation with standardized patients wearing breast jackets for residents to learn and practice CBE. Unlike with medical students [8], the simulation did not impart clinical knowledge, yet residents positively rated the teaching experience, and all agreed that it offered an opportunity to practice and improve their skills. Their recommendations for the inclusion of hybrid simulation in curricula shows their appreciation of the added value of this exercise to practice a sensitive yet important clinical examination, knowing patient encounters are not guaranteed, even during residency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation